Renewable Energy Consumption and Sectoral Based Output - Maji, Ibrahim Kabiru; Saari, Mohd Yusof (International Journal of Finance Research, 2021)
The study explores the effect of renewable energy consumption on sectoral output in the presence of government effectiveness. A regressions method was used to analyze data from 1989 to 2019. The result revealed evidence of the positive and vital impact of renewable energy consumption on the sectoral output of the manufacturing and construction sectors. Although the elasticity of government effectiveness is neutral, trade openness has revealed evidence of positive and significant impact on sectoral outputs. However, population growth does not have a favourable impact on sectoral outputs. Furthermore, renewable energy consumption is not essential in determining the agricultural sector, transportation sector and other sectors. To quickly diversify the economy, policymakers should further increase awareness and provide more incentives for renewable energy in these sectors